Near work, screen time, outdoor time and myopia in schoolchildren in the Sunflower Myopia AEEC Consortium. Issue 3 (17th June 2021) - Lanca, Carla; Yam, Jason C.; Jiang, Wen‐Jun; Tham, Yih‐Chung; Hassan Emamian, Mohammad; Tan, Chuen‐Seng; Guo, Yin; Liu, Hu; Zhong, Hua; Zhu, Dan; Hu, Yuan‐Yuan; Saxena, Rohit; et al.
Abstract: Purpose: To examine the association between near work, screen time including TV and outdoor time with myopia in children from the Sunflower Myopia Asian Eye Epidemiology Consortium (AEEC). Methods: We analysed AEEC cross‐sectional data (12 241 children) on risk factors (near work, screen time including TV and outdoor time) and myopia of six population‐based studies (China, Hong Kong and Singapore). Cycloplegic refraction and axial length (AL) measurements were included. Risk factors were determined using questionnaires. Data were pooled from each study, and multivariable regression analysis was performed to evaluate the associations between risks factors and myopia, spherical equivalent (SE) and AL. Results: Among the included children, 52.1% were boys, 98.1% were Chinese and 69.7% lived in urban areas. Mean±standard deviation (SD) for age was 8.8 ± 2.9 years, for SE was −0.14 ± 1.8 D and for AL was 23.3 ± 1.1 mm. Myopia prevalence was 30.6%. In multivariate analysis, more reading and writing (OR = 1.17; 95% CI, 1.11–1.24), more total near work (OR = 1.05; 95% CI, 1.02–1.09) and less outdoor time (OR = 0.82, 95% CI, 0.75–0.88) were associated with myopia (p's < 0.05). These factors were similarly associated with SE and AL (p's < 0.05), except for total near work and AL (p = 0.15). Screen time including TV was not significantly associated with myopia (p = 0.49), SE (p = 0.49) or AL (p = 0.83). Conclusion: In this study, increased reading and writing and decreased outdoor time were associated with myopia. Screen time may be a surrogate factor of near work or outdoor time, but further research is needed to assess its role as an independent risk factor for myopia.